Stoichiometric interactions explain spindle dynamics and scaling across 100 million years of nematode evolution - Reza Farhadifar; Che-Hang Yu; Gunar Fabig; Hai-Yin Wu; David B Stein; Matthew Rockman; Thomas Müller-Reichert; Michael J Shelley; Daniel J Needleman (eLife, 2020)
The spindle shows remarkable diversity, and changes in an integrated fashion, as cells vary over evolution. Here, we provide a mechanistic explanation for variations in the first mitotic spindle in nematodes. We used a combination of quantitative genetics and biophysics to rule out broad classes of models of the regulation of spindle length and dynamics, and to establish the importance of a balance of cortical pulling forces acting in different directions. These experiments led us to construct a model of cortical pulling forces in which the stoichiometric interactions of microtubules and force generators (each force generator can bind only one microtubule), is key to explaining the dynamics of spindle positioning and elongation, and spindle final length and scaling with cell size. This model accounts for variations in all the spindle traits we studied here, both within species and across nematode species spanning over 100 million years of evolution.